Pigment epithelium detachment with thickened choroid in a preterm infant at term-equivalent age: a case report - Ahn, Seong Joon; Tai, Vincent; Winter, Katrina P.; Sarin, Neeru; Toth, Cynthia A. (Frontiers in Medicine, 2025)
Pigment epithelial detachment (PED) is well-documented in adult retinal diseases but is rarely reported in neonates. This case describes a preterm infant, born at 31 weeks, who developed PED with thickened choroid at term-equivalent age, detected using handheld OCT. The PED emerged at 39 weeks postmenstrual age, coinciding with inhaled steroid treatment for respiratory distress, and resolved by 41 weeks after steroid discontinuation without structural damage. The temporal relationship suggests an association between steroid use and PED with choroidal changes. This case highlights the value of OCT in detecting retinal and choroidal abnormalities in preterm infants and underscores the potential impact of systemic conditions and medications on the choroid.